Gender Education Socialization At The Hidayatussibyan Islamic Boarding School Foundation Nw Sengkerang Year 2024 - Firmansyah, Agung; Sumitro, Sumitro; Adhi, Rakhmat Nur; Utomo, Jepri; Rosyidah, Feryna Nur; Noviana, Mila; Hadi, Mr. Samsul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The activity of providing gender education socialization to students of the Hidayatussibyan NW Sengkerang Islamic Boarding School Foundation is a form of community service implementation targeting students of the Hidayatussibyan NW Sengkerang Islamic Boarding School. Community service in the form of socialization is intended to provide knowledge and awareness building about gender issues such as awareness of gender equality and gender violence. This socialization is expected to raise students' awareness of gender concepts and stereotypes that are developing in society. Based on the results of the community service team's analysis, there are still many students who consider the gender inequality they see in everyday life to be something normal and are not critical of it. The internalization of the values they have received since childhood in their families and the surrounding environment, especially about gender inequality, they consider it commonplace and accept it for granted. This community service is carried out using a direct socialization method and added Focus Group Discussion to find the core of the existing problem. The results of the community service activities are measured through several questions in the form of pre-tests and post-tests, the results of which show an increase and awareness that is starting to build from regarding the students' concept of gender, gender equality, and gender violence.